Species Composition And Spatial Variation Of Benthic Diatoms At Intertidal Zone Under The Influence Of Environmental Parameters - Ahmad Nordin, Noor Alia (2017)
Benthic diatoms play a significant role in the primary productivity and sediment dynamics of coastal and estuarine intertidal ecosystems. Thus, this study aims to determine the spatial distribution of benthic diatoms in intertidal flats from different environmental gradients. The spatial changes of benthic diatom composition under the influence of environmental variables in the tidal flats were studied. Canonical Correspondence Analysis (CCA) was conducted to define the relationships between environmental variables and diatom communities. Sediment samples were collected during low tide at six sampling stations four times in November 2013, February 2014, July 2014 and December 2014 in the coastal area of Tanjung Bungah, and in August 2014, January 2015, May 2015 and September 2015 in Tanjung Rhu, Langkawi estuary.